PERLINDUNGAN HUKUM OLEH KOMISI PENGAWAS PERSAINGAN USAHA (KPPU) DARI PRAKTEK DUMPING AKIBAT PERDAGANGAN INTERNASIONAL - Bhakti, Rizki Tri Anugrah (LPPM Universitas Putera Batam, 2018)
This article discusses the role of the Komisi Pengawas Persaingan Usaha (KPPU) in providing protection for industry in Indonesia from dumping practices due to international trade. Speaking of dumping, it means talking about the practice of selling products in export destination countries at prices below the normal price that have the aim of controlling foreign markets. The consequences of Indonesias participation in international trade organizations will certainly indirectly have the potential to experience impacts on dumping, this is due to the powerlessness of refusing exports from fellow member countries.